2016
DOI: 10.21077/ijf.2016.63.3.48568-12
|View full text |Cite
|
Sign up to set email alerts
|

Textural and functional properties of surimi from striped catfish Pangasianodon hypophthalmus (Sauvage, 1878) as affected by natural spice extracts

Abstract: Effects of aqueous extract of natural spices such as garlic, clove and cinnamon on the textural and functional properties of surimi gel from Striped Catfish, Pangasianodon hypophthalmus (Sauvage, 1878) was studied and a positive effect was observed. Different levels of extract (0.5, 1.0, 1.5 and 2.0%, w/w) were used. Protein solubility significantly (p<0.05) changed in treated gels and major change was found in clove and cinnamon incorporated gels. Water holding capacity of the treated gels were found to be hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Previous work by Majumdar et al. (2016) confirmed that the sensory quality of striped catfish was improved by the application of spices such as garlic, clove, and cinnamon.…”
Section: Resultsmentioning
confidence: 88%
“…Previous work by Majumdar et al. (2016) confirmed that the sensory quality of striped catfish was improved by the application of spices such as garlic, clove, and cinnamon.…”
Section: Resultsmentioning
confidence: 88%